PENGERTIAN DAN PRINSIP-PRINSIP PENDIDIKAN ISLAM SEBAGAI DISIPLIN ILMU - Subandi , Subandi; Syarifuddin Ondeng; Saprin, Saprin (CV. Adiba Aisha Amira, 2024)
Islamic education is a discipline that plays an important role in shaping Muslim individuals and preparing them to face the challenges of modern world life. In this abstract, the basic concepts and principles of Islamic education as a discipline will be discussed. Islamic education is a learning process aimed at forming Muslim individuals who are religiously obedient, moral, noble, and have extensive knowledge of Islam.Islamic education covers not only religious aspects, but also moral, ethical, social, and academic aspects. Islamic education as a discipline has a key role in shaping Muslim individuals who are committed to Islamic teachings and have the ability to make a positive contribution to society. These basic principles form a strong foundation for the development of quality and relevant Islamic education in the context of modern times.